Short-wave infrared cavity resonances in a single GeSn nanowire - Kim, Youngmin (2023)
Nanowires are promising platforms for realizing ultra-compact light sources for photonic integrated circuits. In contrast to impressive progress on light confinement and stimulated emission in III-V and II-VI semiconductor nanowires, there has been no experimental demonstration showing the potential to achieve strong cavity effects in a bottom-up grown single group-IV nanowire, which is a prerequisite for realizing silicon-compatible infrared nanolasers. Herein, we address this limitation and present an experimental observation of cavity-enhanced strong photoluminescence from a single Ge/GeSn core/shell nanowire. A sufficiently large Sn content (~ 10 at%) in the GeSn shell leads to a direct bandgap gain medium, allowing a strong reduction in material loss upon optical pumping. Efficient optical confinement in a single nanowire enables many round trips of emitted photons between two facets of a nanowire, achieving a narrow width of 3.3 nm. Our demonstration opens new possibilities for ultrasmall on-chip light sources towards realizing photonic-integrated circuits in the underexplored range of short-wave infrared (SWIR).